Changes in measures of cervical spine, vestibulo-ocular reflex, dynamic balance and divided attention following sport-related concussion in elite youth ice hockey players - Schneider, K. J.; Meeuwisse, W. H.; Palacios-Derflingher, L.; Emer, C. A. (Journal of Orthopaedic & Sports Physical Therapy, 2018)
Concussion is a commonly occurring injury. The extent to which the cervical spine, vestibulo-ocular reflex (VOR), dynamic balance and divided attention are affected following concussion is not well understood. Objective: To evaluate acute changes in measures of 1) cervical spine, 2) VOR function, 3) dynamic balance and 4) tasks of divided attention in elite youth ice hockey players following a sport-related concussion. Methods: Elite 13-17 year old ice hockey players completed cervical spine measures [cervical flexor endurance test (CFE), head perturbation test, anterolateral strength, cervical flexion rotation test, joint position error], VOR [head thrust test, dynamic visual acuity (DVA) (clinical and computerized)], dynamic balance [Functional Gait Assessment (FGA)] and divided attention [Walking While Talking (WWTT) test] preseason and following concussion. Results: At least one test was completed by 69/97 (71%) players (a maximum of 55 for any one test) at both preseason and acutely post concussion (median 4 days post concussion). After Bonferroni corrections (a=0.00625), using Wilcoxon Signed-Rank Test, cervical spine measures were significantly worse following concussion compared to baseline [CFE (z=-5.20, p<0.00001), anterolateral neck strength (zleft=-5.36, p<0.0001; zright=-5.45, p<0.0001) and head perturbation test (z=-4.63, p<0.001)]. Time taken to complete a complex task of divided attention relative to normal walking speed was faster (improved) compared to preseason (z=-2.59, p=0.0096). There was no change in VOR or dynamic balance following concussion. Conclusions: Measures of cervical spine function and divided attention were altered following concussion. However, tests of VOR and dynamic balance were not significantly different than baseline. Future research to evaluate the mechanism underlying these changes is warranted.